DAMPAK SERTIFIKASI HALAL TERHADAP KEPUTUSAN KONSUMEN MUSLIM DALAM MEMBELI PRODUK MAKANAN (Studi Kasus Pada Masyarakat Kota Pontianak) - Tasya, Nadhifa; Kalbarini, Rahmah Yulisa (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine: 1) The perception of the Pontianak City Muslim community towards halal certification in food products; 2) The impact of halal certification on Muslim consumers decisions in buying food products. This research uses descriptive qualitative method. Source of data comes from primary and secondary data. The primary data in this study are Muslim consumers from various sub-districts in Pontianak City. Secondary data was obtained from books, research journals, articles and documents related to this research. The results obtained from this study include: 1) The perceptions of Muslim consumers in Pontianak City who studied halal certification were very good. They already know the information regarding the halal certification issued by the Indonesian Ulema Council (MUI). Most Muslim consumers in the city of Pontianak state that halal certification of food products is very important. 2) The impact felt by Muslim consumers in the city of Pontianak after seeing halal certification for a food product includes feeling safe, calm, and not hesitating to consume the product because halal certification for a food product has gone through trials and a very long process to prove halal.